Analisis Karakter Disiplin Siswa Kelas V SDN Banyuajuh 2 pada Kegiatan Ekstrakurikuler Pramuka Materi PBB - Qulub, M. Churriyyatul; Puspitasari, Aditya Dyah (Yayasan Arrahman Nahdlatul Wathan, 2024)
The purpose of this research is to determine the discipline characteristics of fifth-grade students at SDN Banyuajuh 2 during the scout extracurricular activities with marching rules material. This research employs a qualitative descriptive method. The subjects used are fifth-grade students. Sampling in this study uses purposive sampling. The research sample consists of 6 fifth-grade students. Data collection methods include observation sheets, interviews, and documentation. The research findings are as follows: In terms of punctuality, students depart on time for scout exercises and school, as observed with all students being punctual both when going to school and during scout exercises. The students perform tasks given by the scout leader promptly. During the marching rules exercises, all students carry out the given tasks from the leader, such as following th commands related to marching rules, correctly and on time. Regarding adherence to rules, students comply with school regulations, as observed with all students adhering to school rules. This is evident from students attending classes on time and participating well. Students also contribute to maintaining environmental cleanliness by participating in cleanliness duties and disposing of waste properly. Additionally, students follow the commands of the scout leader and exhibit perfect behavior when receiving the